Delayed impact of natural climate solutions. (8th November 2020) - Qin, Zhangcai; Griscom, Bronson; Huang, Yao; Yuan, Wenping; Chen, Xiuzhi; Dong, Wenjie; Li, Tingting; Sanderman, Jonathan; Smith, Pete; Wang, Fan; Yang, Song
Abstract : To limit global temperature rise, scientists have proposed significant potentials for climate change mitigation from protecting and managing natural systems. However, depending on the time taken for technology deployment and natural carbon gain, actual mitigation can be dramatically delayed, and total mitigation by 2030 or 2050 can be more than halved compared to the estimated potential. Delayed or lack of action on implementation would push back the timeline to reduce greenhouse gas emissions, largely undermining the Paris goals. Launching actions now and learning from past experience can help deliver climate mitigation and sustainable development goals.